The gentle answer to the Muslim accusation of biblical falsification - Nickel, Gordon D. (Bruton Gate, 2015)
The Gentle Answer is a scholarly response to a claim that many Muslims have made in relation to non-Muslims for more than 1200 years: that the text of the Bible is corrupt and/or falsified. Since critical writing on the Bible is more abundant and has a longer history, Muslim polemicists have selectively used Western biblical criticism in an attempt to support the traditional Muslim accusation of biblical falsification. Only quite recently have the techniques used in biblical criticism been applied to the Qur'an. The Gentle Answer responds to the Muslim claims by placing the Bible and the Qur'an on a level scholarly playing field to show that questions about the Qur'an are at least as challenging as questions about the Bible. The Gentle Answer invites Muslims into a conversation about the contents of the scriptures themselves. Respect for the conversation partner means taking issues of truth seriously. It means doing one's best to thoroughly understand accusations. It also means commending one's own faith in terms of the partner's worldview. Differences in faith between Muslims and non-Muslims show no sign of going away in the years to come. But in a world of considerable political tension and violence, Muslims and non-Muslims must seize the freedom to openly discuss their differences together while nurturing mutual respect and committing to peaceful coexistence. (Back cover)